Tendencias cognitivas y procesos de abstracción en el aprendizaje del Álgebra y de la Geometría - Filloy Yagüe, Eugenio (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
In the present paper we discuss eleven kinds of phenomena which make themselves manifest at the time students are learning new mathematical concepts and operations. These phenomena can be observed both in the classroom and during clinical interviews. When learning mathematics, new rules are constantly being formed, due to the fact that new ways are found to extend conceptual networks previously developed. A central aspect in this point of view is the idea of sense, as opposed to meaning, when speaking about an MSS. In all the comments, we have tried to distinguish between these two notions: meaning and sense.